Determining Phytocomponent of Vetiver Grass (Chrysopogon zizanioides) Under Drought Stress - Ani Sulistiyani; Syamsul Falah; Triadiati Triadiati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2020)
Vetiver grass (Chrysopogon zizanioides, Poaceae) is the leading commodity in Garut Regency, Indonesia, the second-largest producer in the world of vetiver oils. The content of vetiver oils is strongly influenced by the environment, for example, drought stress. Drought stress causes plants to adapt by producing secondary metabolites such as essential oils. This experiment aimed to analyze growth, phytocomponents and obtaining the best quality of vetiver grass accessions under drought stress. The results showed that root and shoot dry biomass were significantly affected by the interaction between drought stress duration and vetiver grass accession. The root dry biomass of Kamojang accession decreased by 25.4%, while Cilawu increased by 5% for 4 days of drought stress. The root length and shoot length were not significantly affected by the treatment. The highest root/shoot length ratio was Verina, and the lowest one was Cisarua. The highest increase in proline occurred in Cilawu accession (85.7%), while the lowest was Verina (6.67%). Essential root oils contain 53 types of phytocomponents, dominated by sesquiterpenes, being khusimol, the highest type. The Cilawu is the best accession based on growth and content rendement.